Differential Expression and Prognostic Correlation of Immune Related Factors Between Right and Left Side Colorectal Cancer - Hu, Yue; Ding, Jie; Wu, Chengjiang; Gao, Hong; Ge, Meiling; Shao, Qixiang; Liu, Yanhong; Ye, Qing (Frontiers in Oncology, 2022)
Background Growing evidence suggests that colorectal cancer (CRC) should be considered a heterogeneous disease. The right side (RCC) and left side (LCC) colorectal cancer have different clinical characteristics and immune landscapes. The aim of this study was to analyze differential expression and prognostic correlation of immune-related factors between RCC and LCC. Methods: The gene expression profile and clinical characteristics of CRC patients were retrieved from TCGA (n=525). Differentially expressed genes (DEGs) were obtained by performing differential gene expression analysis. To further validate the findings, we applied immunohistochemical (IHC) staining of a CRC tissue microarray (TMA). The immune function of immune cells in LCC and RCC was verified by flow cytometry to detect the cytokines secreted by immune cells. Survival analysis based on mRNA levels using TCGA cohort and survival analysis using protein levels was performed using our CRC patients. Results: The infiltration of immune cells differed between RCC and LCC, CD4+ T and CD8+ T cells were significantly more expressed in RCC than in LCC, macrophages M0 were significantly more expressed in LCC than in RCC, while differentiated macrophages M1 and M2 were more expressed in RCC. The expression of related molecules in immune cells also differed between RCC and LCC. Nine immune-related DEGs were selected by data analysis. Patients with RCC having high expression of HLA-DQA1 mRNA or proteins had better survival and LCC patients with high expression of IL 34 mRNA or protein had better survival. As an MHC II molecule, HLA-DQA1 plays an important role in the specific immune regulation mechanism in RCC by binding to the TCR on the surface of CD4+ or CD8+ T cells to promote an adaptive immune response. The immune-related factor IL-34, secreted by M0 macrophages and endothelial cells, plays an important role in the innate immune regulation mechanism. Conclusions: In this study, we comprehensively compared differences in immune cells and regulating factors between left and right colorectal cancer. Different expression patterns and function and their effects on survival and immunomodulatory mechanisms were also identified. The analysis of immune-related factors may provide a theoretical basis for precise immunotherapy of RCC and LCC.